Hospital Pharmacy in the multidisciplinary team of COVID inpatient units - María Victoria Gil-Navarro; Rafael Luque-Márquez (Farmacia Hospitalaria)
Since the implementation of the Antimicrobial Therapy Optimization Programme, hospital pharmacy specialists have collaborated with infectious disease specialists on a regular basis in most hospitals in Spain. Cooperation between these professionals ensures the integrated management of patients with infectious diseases and the appropriate use of antimicrobials in hospitals. The COVID-19 pandemic forced hospital pharmacists to abruptly suspend all their structured activities and concentrate on the health crisis. Realtime information sharing between different medicine specialties is an effective strategy to generate and maintain treatment protocols adapted to each center, with continuous evidence-based modifications as new publications appear. Hospital pharmacies had to reorganize their activities to respond to the pandemic. On the one side were patients with COVID-19, and on the other were routine hospital pharmacy tasks, with the added difficulty of adapting to individual protection measures. New communication and collaboration strategies were adopted. Protocols were established for the management of COVID-19 patients, with continuous changes, special medications had to be prepared and distributed, circuits were designed for the home- or institution-based care of patients, internal circuits were created to minimize the movements of hospital staff and professionals caring for COVID-19 patients. The most effective antiviral drug and anti inflammatory therapy remains elusive. In this scenario, hospital pharmacists emerge as a key player, as they have a deep understanding of the mechanisms of action of drugs and potential interactions. In a setting where experimental drugs preferably tested in clinical trials are being used, the role of hospital pharmacists in interdisciplinary teams has become essential for the optimization of clinical outcomes.